Synthesis of 1,3-thiazole derivatives - Omar, Rebaz; Koparir, Pelin; Koparir, Metin (Indian Drug Manufacturers' Association, 2021)
Many heterocyclic compounds containing nitrogen atom are used in drug development. Thiazole is one of the most important heterocyclic compounds in drug design, which contains sulfur and nitrogen atom. Different site reactions in thiazole compounds extend to new drug synthesis and plays an important role in medicinal chemistry. Thiazole and derivatives are found to possess widely biological activities such as anti-inflammatory, anti-diabetic, anti-microbial, anti-cancer, anti-convulsant, anti-HIV, anti-hypertensive, anti-Alzheimer, anti-oxidant and anthelmintic. The aim of this review is to corroborate procedures which are available for the synthesis 1,3-thiazole derivatives. © 2021 Indian Drug Manufacturers' Association. All rights reserved.
Keywords: 3-thiazoles; Substitutedthiazole; Synthesis1; Thiazole derivatives